Immunological characteristics of patients with latent tuberculosis infection (Ta'limning zamonaviy transformatsiyasi, 2024)
From the WHO report for 2020 Until now, the problem of tuberculosis has not been solved in any country in the world and remains a priority public health task. According to WHO data, in 2020, 10.0 million people fell ill in the world , including 5.6 million men, 3.2 million women, 1.2 million children. In 2021 - 9.9 million, including : 5.5 million men, 3.3 million women, 1.1 million children, 1.3 million people with HIV-negative status, died from tuberculosis. 214,000 HIV-positive from tuberculosis. The number of patients with MDR and XDR is growing from year to year. Tuberculosis is still one of the 10 main causes of death from a single pathogen.